THE REPRESENTATION OF BULLYING IN AMERICAN FILMS - Br. Ginting, Greace Naomi; Rudy, Rudy (Rubikon : Journal of Transnational American Studies, 2023)
The issue of bullying continues to be reported by the media because it still happens everywhere, especially in schools, and needs to be discussed in research. This qualitative research focuses on studying American films with the theme of bullying, namely Bully (2011), A Girl Like Her (2015), and Wonder (2017) as the main source of data. This study aims to identify how American movies portray bullying and to find out what bullying represents by applying Hall’s representation theory. Dialogs collected and sorted from the films were treated as signs that would convey more meanings. The results of data analysis suggest that American films with the themes of bullying frequently show bullying through portraits of physical violence, verbal violence, and trauma. Besides, bullying can also indicate a lack of attention from the family, the condition of the social environment, and the powerlessness of humans.